Shear deformation of pure-Cu and Cu/Nb nano-laminates using micromechanical testing. (June 2023) - Ajantiwalay, Tanvi; Ma, Xiaolong; Yu, Anqi; Pole, Mayur; Silverstein, Joshua; Mathaudhu, Suveen; Devaraj, Arun; Gwalani, Bharat
Abstract: Solid phase processing by introducing shear deformation into materials can result in unique microstructure evolution and enhanced mechanical properties, especially for immiscible systems such as Cu/Nb. To better understand the correlation between microstructure and deformation behavior during shear, a dedicated testing design of stress localization at predicted sites is necessary. In this study, a specialized S-shaped specimen geometry is implemented to apply localized simple-shear loading in pure-Cu and Cu/Nb accumulative roll-bonded nanolaminates. The nanoscale microstructure and proximity of interfaces in Cu/Nb offer a ∼2.8-fold increase in shear stresses than pure-Cu. In pure-Cu, the plastic instability causes shear banding and an in-plane lattice rotation. In Cu/Nb, a partial bending of the interfaces occurred, resulting in a localized lattice rotation. The adapted geometry for micro-scale specimens thus successfully captures the shear deformation at predicted sites in two distinct material systems and could potentially be a powerful technique to study the deformation mechanisms. Graphical abstract: Image, graphical abstract